Sistem Informasi Pemasaran Perumahan Pada PT. Trixie Graha Anugerah Berbasis Web - Darmawan Laoli; Titin Kristiana (LPPM Universitas Bina Sarana Informatika, 2022)
PT. Trixie Graha Anugerah is one of the companies in Bekasi Regency involved in the construction and marketing of housing. PT. Trixie Graha Anugerah continues to use traditional marketing methods in its marketing activities. Several traditional marketing methods have been used in the past, such as printing and distributing brochures, hiring marketing personnel, and setting up booths in congested areas. The author evaluates the conventional marketing methods used at PT. Trixie Graha Anugerah to be less effective and efficient. Conventional marketing methods are ineffective because they cannot reach a large number of potential consumers, and they are inefficient because they require large sums of money to print promotional materials such as brochures, as well as costs to rent stands in congested areas